1931 Ill. Laws 453 - (:unkn) unknown (My University, 1931)
An Act to Regulate the Sale, Possession and Transportation of Machine Guns, § 4: Required every manufacturer or merchant to keep a register of all machine guns manufactured or handled. Data kept includes the sale, loan, gift, delivery, or receipt of any machine gun, the name, address, and occupation of the person to whom the machine gun was delivered, from whom it was received, and why it was sold, loaned, given, delivered, purchased, or obtained said machine gun. Law enforcement shall have on-demand access to these records.
Keywords: MACHINE GUN RESTRICTION